2016
DOI: 10.1016/j.ophtha.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

North Carolina Macular Dystrophy Is Caused by Dysregulation of the Retinal Transcription Factor PRDM13

Abstract: Purpose To identify specific mutations causing North Carolina Macular Dystrophy (NCMD). Study Design Whole genome sequencing coupled with RT-PCR analysis of gene expression in human retinal cells. Subjects 141 members of 12 families with NCMD and 261 unrelated control individuals. Methods Genome sequencing was performed on eight affected individuals from three families affected with chromosome-6-linked NCMD (MCDR1) and two individuals affected with chromosome-5-linked NCMD (MCDR3). Variants observed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
168
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(173 citation statements)
references
References 52 publications
4
168
1
Order By: Relevance
“…Additionally, gene-level analysis did not detect exonic or splice site variants in the same gene for two or more families. Therefore, non-coding causes were predicted as a common mechanism, as has been reported for MCDR1 and MCDR3 [13, 14]. Genome-wide analysis was performed for family 4 using SNP chips.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, gene-level analysis did not detect exonic or splice site variants in the same gene for two or more families. Therefore, non-coding causes were predicted as a common mechanism, as has been reported for MCDR1 and MCDR3 [13, 14]. Genome-wide analysis was performed for family 4 using SNP chips.…”
Section: Resultsmentioning
confidence: 92%
“…The ERG and EOG are also normal in NCMD, with dysfunction being confined to the macula. Recently, Small et al identified rare variants upstream of the retinal transcription factor gene PRDM13 in families with NCMD that link to the MCDR1 locus [14]. An identical phenotype has been mapped to chromosome 5p15 (MCDR3 locus) [16], [17].…”
Section: Discussionmentioning
confidence: 99%
“…The striking observation that 79% of cases with molecular diagnoses are accounted for by mutations in genes discovered between 1995 and 2004 suggests that while the continued addition of new disease-causing genes will of course improve diagnostic services, the comprehensive evaluation of protein-coding and regulatory variants affecting known disease-causing genes may have a greater influence on diagnostic yield. For example, the genomic sequencing of genes known to cause IRD has identified large deletions,14 deeply intronic disease-causing mutations31 and variants in regulatory regions,32 which would elude traditional custom panel NGS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Linkage studies have mapped MCDR1 to a locus on chromosome 6q16 which has latterly been refined to a 1.8 mb region (Yang et al, 2008). Just this year, Small and colleagues applied whole genome sequencing techniques to identify variants which segregate with the disease (Small et al, 2015). Bioinformatic filtering followed by segregation and gene expression studies have now implicated PRDM13 as the gene underlying the MCDR1 locus, a transcription factor now understood to be critical for macular development.…”
Section: North Carolina Macular Dystrophy and Ncmd-like Disordersmentioning
confidence: 99%